Optical Coherence Tomography Findings in Patients With Coronary Stent Thrombosis: A Report of the PRESTIGE Consortium (Prevention of Late Stent Thrombosis by an Interdisciplinary Global European Effort). Issue 11 (12th September 2017) - Adriaenssens, Tom; Joner, Michael; Godschalk, Thea C.; Malik, Nikesh; Alfonso, Fernando; Xhepa, Erion; De Cock, Dries; Komukai, Kenichi; Tada, Tomohisa; Cuesta, Javier; Sirbu, Vasile; Feldman, Laurent J.; et al.
Abstract : Background: Stent thrombosis (ST) is a serious complication following coronary stenting. Intravascular optical coherence tomography (OCT) may provide insights into mechanistic processes leading to ST. We performed a prospective, multicenter study to evaluate OCT findings in patients with ST. Methods: Consecutive patients presenting with ST were prospectively enrolled in a registry by using a centralized telephone registration system. After angiographic confirmation of ST, OCT imaging of the culprit vessel was performed with frequency domain OCT. Clinical data were collected according to a standardized protocol. OCT acquisitions were analyzed at a core laboratory. Dominant and contributing findings were adjudicated by an imaging adjudication committee. Results: Two hundred thirty-one patients presenting with ST underwent OCT imaging; 14 (6.1%) had image quality precluding further analysis. Of the remaining patients, 62 (28.6%) and 155 (71.4%) presented with early and late/very late ST, respectively. The underlying stent type was a new-generation drug-eluting stent in 50.3%. Mean reference vessel diameter was 2.9±0.6 mm and mean reference vessel area was 6.8±2.6 mm 2 . Stent underexpansion (stent expansion index <0.8) was observed in 44.4% of patients. The predicted average probability (95% confidence interval) that any frame had uncovered (or thrombus-covered) struts was 99.3% (96.1–99.9), 96.6% (92.4–98.5), 34.3% (15.0–60.7), and 9.6% (6.2–14.5) and malapposed struts was 21.8% (8.4–45.6), 8.5% (4.6–15.3), 6.7% (2.5–16.3), and 2.0% (1.2–3.3) for acute, subacute, late, and very late ST, respectively. The most common dominant finding adjudicated for acute ST was uncovered struts (66.7% of cases); for subacute ST, the most common dominant finding was uncovered struts (61.7%) and underexpansion (25.5%); for late ST, the most common dominant finding was uncovered struts (33.3%) and severe restenosis (19.1%); and for very late ST, the most common dominant finding was neoatherosclerosis (31.3%) and uncovered struts (20.2%). In patients presenting very late ST, uncovered stent struts were a common dominant finding in drug-eluting stents, and neoatherosclerosis was a common dominant finding in bare metal stents. Conclusions: In patients with ST, uncovered and malapposed struts were frequently observed with the incidence of both decreasing with longer time intervals between stent implantation and presentation. The most frequent dominant observation varied according to time intervals from index stenting: uncovered struts and underexpansion in acute/subacute ST and neoatherosclerosis and uncovered struts in late/very late ST. Abstract : Supplemental Digital Content is available in the text.